2019
DOI: 10.1038/s41438-019-0194-7
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of transcriptomic and proteomic data from tree peony (P. ostii) seeds reveals key developmental stages and candidate genes related to oil biosynthesis and fatty acid metabolism

Abstract: Tree peony (Paeonia section Moutan DC.) seeds are an excellent source of beneficial natural compounds that promote health, and they contain high levels of alpha-linolenic acid (ALA). In recent years, tree peony has been emerging as an oil crop. Therefore, combined analysis of the transcriptome and proteome of tree peony (P. ostii) seeds at 25, 32, 39, 53, 67, 81, 88, 95, and 109 days after pollination (DAP) was conducted to better understand the transcriptional and translational regulation of seed development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 67 publications
1
67
0
Order By: Relevance
“…4 and 5). In a previous study, genes related to fatty acid biosynthesis were grouped into two categories and detected in the early or later stages of seed development in tree peony [49]. Similarly, the coordinated regulation of multiple genes has been shown to promote the high accumulation of longchain unsaturated fatty acids in the seeds of tea oil camellia [50], and consistent results have been obtained in Brassica napus [51,52], Glycine max [53], and Linum usitatissimum [54].…”
Section: Discussionmentioning
confidence: 61%
“…4 and 5). In a previous study, genes related to fatty acid biosynthesis were grouped into two categories and detected in the early or later stages of seed development in tree peony [49]. Similarly, the coordinated regulation of multiple genes has been shown to promote the high accumulation of longchain unsaturated fatty acids in the seeds of tea oil camellia [50], and consistent results have been obtained in Brassica napus [51,52], Glycine max [53], and Linum usitatissimum [54].…”
Section: Discussionmentioning
confidence: 61%
“…At present, the research has focused on the analysis of fatty acid in tree peony seed oils [2][3][4]. Another category of important nonpolar compounds, phytosterols, has not been reported in tree peony seed oil to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…There are nine wild species in section Moutan DC, which differ with respect to preferred habitat, but all rich in unsaturated FAs (>90%) and ALA (26.7-50%) [6,9]. To date, transcriptomic, proteomic, and microRNA sequencing have been used to investigate the mechanisms underlying ALA synthesis in tree peony seeds [10][11][12][13][14]. Previous studies have focused on enzymes that are key to ALA biosynthesis in various tree peony species, including FAD3 in P. rockii, P. potaninii and P. lutea seed [15]; FAD2 and FAD8 in P. ostii [10]; and ACCase, FATA, LPCAT, FADs, and DGAT in the developing endosperm of P. ostii var.…”
Section: Introductionmentioning
confidence: 99%
“…lishizhenii [11]. Wang et al [14] identified 115 genes and 24 proteins associated with the ALA metabolism in P. ostii seeds. However, despite these studies of FA metabolism in the tree peony, additional functional genes require further exploration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation